Safety and Long-Term Efficacy Outcomes for Endovascular Treatment of Wide-Neck Bifurcation Aneurysms of the Middle Cerebral Artery: Insights From the SMART Registry - De Leacy, Reade; Bageac, Devin V.; Siddiqui, Neha; Bellon, Richard J.; Park, Min S.; Schirmer, Clemens M.; Woodward, Keith B.; Zaidat, Osama O.; Spiotta, Alejandro M. (Frontiers in Neurology, 2022)
Introduction: Wide-necked middle cerebral artery bifurcation aneurysms pose specific challenges to endovascular management. Surgical clipping remains the standard treatment approach for these aneurysms in many centers. While recent data suggests the endovascular treatment may be comparable, a prospective datapoint has been lacking. Materials and Methods: The Penumbra SMART registry, a prospective, multi-center, single-arm outcomes registry of Penumbra coil-treated aneurysms, was queried for endovascularly treated MCA bifurcation aneurysms with wide necks (dome:neck ratio < 2 or neck > 4mm). Safety and efficacy outcomes were summarized for ruptured and unruptured aneurysms, including rupture, complication rate, and 1-year occlusion outcomes. Results: Seventy-two aneurysms across 31 sites were enrolled. Of these, a total of 15 presented as ruptured aneurysms. Serious adverse events were reported in 21 (29.2%) of patients, with 8 (11.1%) attributed to the device/procedure. Immediately postoperatively, 75.0% of cases achieved “adequate” Raymond Roy Class I (40.3%) or II (34.7%) occlusion outcomes. Of the 72 patients treated, 60 (83.3%) underwent follow-up angiography at one year, and among these, 95.0% had 1-year occlusion outcomes of Raymond Roy Class I (71.7%) or II (23.3%). A total of 6 aneurysms (10.0%) were required or were planned for retreatment at the last follow-up. Conclusion: This study represents the most significant prospective sample of endovascularly treated wide-neck MCA bifurcation aneurysms conducted to date. It supports the safety and efficacy of endovascular treatment of these aneurysms.